2021
DOI: 10.1111/acem.14404
|View full text |Cite
|
Sign up to set email alerts
|

Salary disparities based on gender in academic emergency medicine leadership

Abstract: Objective There are significantly fewer women than men in leadership roles in health care. Previous studies have shown that, overall, male physicians earn nearly $20,000 more annually than their female physician colleagues after adjusting for confounding factors. However, there has not been a description of physician leadership compensation in relation to gender. Methods This was a successive cross‐sectional observation study design of 154 emergency departments in the United States from 5 years (2013, 2015–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 16 publications
3
9
0
Order By: Relevance
“…In the academic community, female physicians in academic emergency medicine work more clinical hours, are paid less, and hold fewer leadership roles. 12,[26][27][28][29] Our findings are also consistent with a longitudinal study of academic emergency physician income, which found persist gender-based pay gaps between 2013 and 2017. 28 The underlying cause of this persist gap is unclear.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the academic community, female physicians in academic emergency medicine work more clinical hours, are paid less, and hold fewer leadership roles. 12,[26][27][28][29] Our findings are also consistent with a longitudinal study of academic emergency physician income, which found persist gender-based pay gaps between 2013 and 2017. 28 The underlying cause of this persist gap is unclear.…”
Section: Discussionsupporting
confidence: 89%
“…Using similar methodology over the same time period, Weeks and Wallace found an average gender‐based gap for emergency physicians of $47,854, 14 ‐ a gap that has persisted into the 2020s according to our findings. In the academic community, female physicians in academic emergency medicine work more clinical hours, are paid less, and hold fewer leadership roles 12,26–29 . Our findings are also consistent with a longitudinal study of academic emergency physician income, which found persist gender‐based pay gaps between 2013 and 2017 28 .…”
Section: Discussionsupporting
confidence: 86%
“…Even though women are still underrepresented as speakers at the SSERM conferences, there is a favourable upward trend. However, Wiler et al found that women worked more clinical hours and were paid less when holding leadership roles in academic emergency medicine compared with men [15]. Proposed strategies to increase diversity in healthcare and academic leadership in emergency medicine include early career planning with senior faculty members, establishing and continuously expanding a mentorship network as well as overcoming misalignments of one's own experiences and goals and the priorities of the working institution [16].…”
Section: Discussionmentioning
confidence: 99%
“…3,4 A study from 2020 based on data from the Association of American Medical Colleges demonstrated that over a 35-year period, women physicians in academic medical centers were less likely than men to be promoted to the rank of associate professor, full professor, or department chair with no apparent narrowing of this gap over time. [5][6][7][8] Women in academic EM are paid significantly less, but work more clinical hours than their male colleagues 9,10 and are more prone to gender discrimination. 11 Women trainees in EM are even more vulnerable to bias, with robust data reflecting differences in selection and matriculation, [12][13][14][15] faculty and nursing evaluation of performance, [16][17][18] patient perception, 19 and attrition.…”
Section: Introductionmentioning
confidence: 99%